Characterisation of nasal Staphylococcus delphini and Staphylococcus pseudintermedius isolates from healthy donkeys in Tunisia. (14th August 2014) - Gharsa, H.; Slama, K. Ben; Gómez‐Sanz, E.; Gómez, P.; Klibi, N.; Zarazaga, M.; Boudabous, A.; Torres, C.
Summary: Reasons for performing study: Staphylococcus intermedius group (SIG) bacteria can colonise the nares of some animals but are also emerging pathogens in humans and animals. Objectives: To analyse SIG nasal carriage in healthy donkeys destined for food consumption in Tunisia and to characterise recovered isolates. Methods: Nasal swabs from 100 healthy donkeys were tested for SIG recovery, and isolates were identified by biochemical and molecular methods. Antimicrobial susceptibility of isolates was tested and detection of antimicrobial resistance and virulence genes was performed. Isolates were typed at the clonal level by multilocus sequence typing and Sma I pulsed‐field gel electrophoresis. Results: Staphylococcus delphini and Staphylococcus pseudintermedius (included in SIG) were obtained in 19% and 2% of the tested samples, respectively, and one isolate per sample was characterised. All isolates were meticillin susceptible and mecA negative. Most S. delphini and S. pseudintermedius isolates showed susceptibility to all antimicrobials tested, with the exception of 2 isolates resistant to tetracycline ( tet (M) gene) or fusidic acid. The following toxin genes were identified (percentage of isolates): lukS‐I (100%), lukF‐I (9.5%), siet (100%), se‐int (90%), seccanine (19%) and expA (9.5%). Thirteen different pulsed‐field gel electrophoresis profiles were identified among the 21 SIG isolates. Additionally, the following 9 different sequence types (STs) were detected by multilocus sequence typing, 6 of them new: ST219 (6 isolates), ST12 (5 isolates), ST220 (3 isolates), ST13, ST50, ST193, ST196, ST218 and ST221 (one isolate each). Conclusions: Staphylococcus delphini and S. pseudintermedius are common nasal colonisers of donkeys, generally susceptible to the antimicrobials tested; nevertheless, these SIG isolates contain virulence genes, including the recently described exfoliative gene ( expA ) and several enterotoxin genes, with potential implications for public health. This is the first description of S . delphini in Tunisia. The Summary is available in Chinese – see Supporting information .